Purification, production of antiserum and development of enzyme linked immunosorbent assay-based diagnosis for Cucumber mosaic virus infecting black pepper (Piper nigrum L.) - Hareesh, R P Pant, A I Bhat, T H Faisal, R Madhubala, P S (Journal of Spices and Aromatic Crops, 2004)
Cucumber mosaic virus (CMV) infecting black pepper (Piper nigrum) in India was propagated on Nicotiana benthamiana and N. glutinosa, and purified by differential and sucrose densitygradient centrifugation. The purified virus preparations showed the presence of typical isometric particles of about 28 nm diameter. Polyclonal antiserum against the virus was produced in New Zealand white rabbits. Immunoglobulin G was purified from the crude antiserum and coupled with the enzyme, alkaline phosphatase. 'Double antibody sandwich-enzyme linked immunosorbent assay method was standardized for detection of CMV in diseased black pepper samples collected from different regions of Karnataka, Kerala and Tamil Nadu. The virus infection was also detected on other Piper species such as P. chaba, P. colubrinum and P. longum and a few of the common weeds such as Ageratum conyzoides, Colacasia esculanta, Synedrella nodiflora, Cynodon dactylon and Sonchus oleraceus found in and around black pepper gardens. The utility of the method developed in diagnosis, epidemiology and management of the disease is discussed.